Pengaruh Hambatan Kerja Sama Instansi Pemerintah: Studi Atas Nota Kesepahaman dan Perjanjian Kerja Sama - Yuliana, Risma; Shebubakar, Arina Novizas; Lutfi, Anas (Publikasi Indonesia, 2025)
In government institutions, cooperation agreements are formalized through the signing of a Memorandum of Understanding (MoU), followed by a Cooperation Agreement. However, the process of reaching the signing of the MoU and Cooperation Agreement, as well as the implementation of the agreed activities, does not always run smoothly. Several issues and obstacles may arise. This study aims to analyze the impact of obstacles in cooperation within government institutions based on the MoU and Cooperation Agreement. A descriptive qualitative research method was used, with data collected through questionnaires via Google Forms and interviews. The research findings indicate that the main obstacles in cooperation include communication, coordination, human resources, and activity budgeting. Recommended solutions include forming a coordination team, preparing adequate human resources, and planning a more flexible budget. Understanding these obstacles and their impacts is useful for minimizing errors when renewing or initiating new cooperation agreements with other parties, thus ensuring more effective and optimal cooperation implementation.